Effectiveness Analysis of Indonesia's Port State Control Inspection Under Tokyo MOU: A Mixed-Methods Approach - Femmy Sofie Schouten; M. Adil Wanadi; Wisnu Wardana Kusuma; Agus Pramono; Dandun Prakosa; Rio Laksamana (Meteor STIP Marunda, 2025)
Port State Control (PSC) is a critical mechanism for ensuring maritime safety, environmental protection, and compliance with international shipping regulations. As a member of the Tokyo Memorandum of Understanding (Tokyo MOU), Indonesia conducts PSC inspections to monitor foreign vessels operating in its waters. This study examines the effectiveness of Indonesia's PSC inspections under the Tokyo MOU framework, analyzing ship detention trends, common deficiencies, and regulatory enforcement challenges. A mixed-methods approach is employed, combining quantitative analysis of PSC inspection and detention data from recent years with qualitative assessments of inspection procedures and regulatory frameworks. Findings indicate that while Indonesia has improved PSC implementation, challenges persist in inspection consistency and resource limitations. The study highlights the need for enhanced coordination among maritime authorities, improved inspector training, and stricter regulatory compliance to optimize inspection effectiveness. The research concludes that a more rigorous and consistent PSC approach will contribute to safer maritime operations and reduced environmental risks. This study contributes to maritime safety literature by providing insights into PSC implementation in a developing maritime nation, along with policy recommendations to strengthen regulatory practices and advance global maritime safety standards.